ANALISIS RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PT. SENTRA FOOD INDONESIA TBK PERIODE 2020 - 2023 - Nurainun Tanjung; Fichra Azrina Arniz; Yuyun Pazra Audita Manurung (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The study aims to evaluate the financial performance of PT Sentra Food Indonesia Tbk by analyzing its financial statements and assessing its financial condition using financial ratio methods. This research includes an analysis of liquidity and solvency ratios. The information and data used were obtained from the company's official financial statements over a specific period, which are accessible on its official website. The findings reveal that the company's financial performance fluctuates annually, with some indicators showing improvements and strengths, while others highlight potential financial risks. The liquidity ratio reflects the company's ability to consistently meet its short-term obligations, although occasional financial pressures are noted. The solvency ratio illustrates the company's capability to fulfill both long-term and short-term financial obligations, particularly in the event of liquidation. This study provides efficient solutions for addressing the financial state of PT Sentra Food Indonesia Tbk and offers strategic recommendations to enhance the company's financial stability